Delivery of Therapeutic Agents to the Central Nervous System and the Promise of Extracellular Vesicles - Charlotte A. René; Robin J. Parks (MDPI AG, 2021)
The central nervous system (CNS) is surrounded by the blood-brain barrier (BBB), a semipermeable border of endothelial cells that prevents pathogens, solutes and most molecules from non-selectively crossing into the CNS. Thus, the BBB acts to protect the CNS from potentially deleterious insults. Unfortunately, the BBB also frequently presents a significant barrier to therapies, impeding passage of drugs and biologicals to target cells within the CNS. This review provides an overview of different approaches to deliver therapeutics across the BBB, with an emphasis in extracellular vesicles as delivery vehicles to the CNS.